PELATIHAN PENGELOLAAN MEDIA SOSIAL (INSTAGRAM) BAGI PELAKU UMKM DI KABUPATEN SAMOSIR - Rizki Christian Sipayung; Romindo M Pasaribu; Vinsensius Matondang (Jurnal Abdimas Bina Bangsa, 2023)
Social media plays an important role in the sustainability of MSME. However, until now, there are still many MSMEs who do not understand the importance of social media management, especially Instagram. Even though this is very useful for the business development of MSME actors, Knowledge about the use of social media by MSMEs is considered feasible and important to understand because it will add brand awareness and value to these MSMEs. This service focuses on developing insights and social media management skills (Instagram) using Canva for MSMEs. MSME players are equipped with insight into the importance of managing social media by creating interesting content using Canva. MSME players can distinguish content that is suitable for the persona or character of the target market to be achieved